Application of Cubic Spline in Earthquake Risk Modelling in Indonesia and Its Relation to Insurance Claim at PT. Jasa Raharja Insurance Company - rifki saefullah (Universitas Ahmad Dahlan, 2026)
Earthquakes with a magnitude exceeding 5.0 on the Richter Scale are events that raise serious concerns for every country, as such earthquakes can result in considerable damage. Earthquakes within the 5.5 to 6.0 SR range can cause minor damage to buildings and infrastructure, while those ranging from 6.1 to 6.9 SR may result in significant destruction in densely populated areas. Meanwhile, earthquakes measuring between 7.0 and 7.9 SR are classified as major earthquakes capable of causing severe structural damage. As a result, many individuals (policyholders) choose to insure their assets with insurance companies. Policyholders pay a certain amount of premium to the insurer (insurance company) in exchange for financial compensation (claims) for any insured events that occur. This research focuses on modeling earthquake intensity in Indonesia using Cubic Spline Interpolation and analyzing its relationship with the number and magnitude of claims at PT. Jasa Raharja. Cubic Spline Interpolation is a mathematical method used to generate smooth functions that pass through a set of given data points. The findings indicate that large insurance claims at PT. Jasa Raharja are significantly correlated with the occurrence of earthquakes in Indonesia. This study provides insights into earthquake events in Indonesia and their implications for insurance companies, which can serve as a reference for disaster risk mitigation strategies in Indonesia.